Онлайн обучение в условиях пандемии (Heteroglossia – studia kulturoznawczo-filologiczne, 2021)
The article is co-authored and analyses the issues of student satisfaction with the format of online learning, their views on its future, identifies the main difficulties and problems of students in the process of transition to online learning. In this article, the authors review the results of the survey and propose ways to solve the considered problems of online learning. The article highlights the possible practical use of the results by transforming the current education model, adjusting the existing academic curricular, making changes when preparing to university classes, etc.